Investigation of asymptomatic temporomandibular disorders with Fonseca anamnestic index in clinical practice - Deniz YAMAN; Cansu ALPASLAN; Oya KALAYCIOĞLU (Gazi University, 2021)
Objective: The study aims to evaluate the presence of temporomandibular disorders (TMD) and their severity in asymptomatic and healthy individuals using the Fonseca anamnestic index. Materials and Method: A total of 135 individuals (80 females and 55 males, mean age 34.4±10.9) were involved in the study. The Fonseca anamnestic index was administered to the individuals. The data analysis was conducted by using Pearson's chi-squared test, Fisher's exact test, one-way ANOVA, and Spearman's correlation. Results: TMD was detected in 63% of the individuals. Most of them (40%) had mild TMD. The difference between gender and TMD severity was statistically significant (p=0.001). Temporomandibular joint (TMJ) pain showed a statistically significant positive correlation with headache and emotional stress (r=0.312, p˂0.001; r=0.299, p˂0.001, respectively). TMJ pain showed the strongest positive correlation with clicking (r=0.443, p˂0.001). Bruxism showed positive correlations with the TMJ pain and clicking (r=0.197, p=0.022 and r= 0.221, p=0.010, respectively). Conclusion: The Fonseca anamnestic index is a reliable diagnostic tool that can be used to detect TMD-related symptoms and severity even in asymptomatic and healthy participants, providing rapid results in clinical practice.